COLLECTION-BASED RESEARCH ON A KAMPILAN SWORD IN JAMBI PEOPLE’S STRUGGLE MUSEUM - Leihitu, Irsyad; Hariadi, Ujang (UI Scholars Hub, 2023)
This article discusses the kampilan sword in Jambi People’s Struggle Museum. Kampilan is a traditional weapon originating from the Philippines but has spread to several regions in Indonesia, including Jambi. The kampilan sword collection is often overlooked, and there is not much information regarding these objects, despite the museum’s primary function is research and communication. Therefore, we conducted a study of a collection of kampilan swords to explore information related to these objects, allowing the museum to utilize and develop them in the future. The research model was based on the material culture study, using the social life of things and object biography approaches. Results indicate that, through these two approaches, new information and narratives about kampilan swords were successfully compiled. In the future, the museum can use these narratives to create new programs, create meanings and ideas related to struggle, and serve as the first step towards further research.